Judge's Dilemma in Determining Bankruptcy Decisions: Dichotomy Between Supreme Court Circular Letter Number 3 of 2023 and Law 37 of 2004 Concerning Bankruptcy- PKPU - M.O. Saut Hamonangan Turnip; Geofani Milthree Saragih; Evanto Pandora Manalu (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
This study aims to examine the dilemma faced by judges in determining bankruptcy decisions, especially in the context of conflict between Supreme Court Circular Letter Number 3 of 2023 and Law 37 of 2004 concerning Bankruptcy-PKPU. The research method used is a normative research method that focuses on analyzing laws and regulations, court decisions, and related legal documents. This approach allows researchers to understand and analyze relevant legal aspects to obtain a comprehensive understanding of the judge's dilemma in determining bankruptcy decisions. In the context of normative research, the researcher conducted an in-depth study of the conflict between Supreme Court Circular Letter Number 3 Year 2023 and Law 37 Year 2004 on Bankruptcy-PKPU. This research explores how judges face the challenge of applying different regulations and their potential impact on their decisions. The analysis is conducted with reference to applicable legal principles, legal interpretations, as well as relevant cases in court practice. The results of this study are expected to contribute to clarifying the framework of thought and legal solutions to the problem of judges' dilemma in the context of bankruptcy in Indonesia. In addition, this research can also serve as a basis for stakeholders, both legal practitioners and policy makers, to consider the necessary steps to minimize legal conflicts and improve consistency and fairness in handling bankruptcy cases.